2018
DOI: 10.1177/2325967118781328
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Deep Vein Thrombosis or Pulmonary Embolus Following Anterior Cruciate Ligament Reconstruction

Abstract: Background:Nearly 350,000 Americans develop a deep venous thromboembolism (DVT) or pulmonary embolism (PE) annually, and nearly 100,000 Americans die from these events. To date, little research has investigated patient-specific risk factors that increase the rate of DVT/PE following anterior cruciate ligament reconstruction (ACLR).Purpose:To determine relevant patient risk factors for the development of DVT/PE following ACLR.Study Design:Case-control study; Level of evidence, 3.Methods:All instances of ACLR fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 26 publications
(26 reference statements)
2
20
0
Order By: Relevance
“…In our multivariate analysis, the factors including age, hypertension, hyperlipemia, radiotherapy, and adenocarcinoma were independent risk factors for DVT in patients with gynecological malignant tumor. In a review of 9146 patients undergoing anterior cruciate ligament reconstruction, Bokshan suggested that increasing age over 30 years and hypertension were associated with an increased risk of DVT 13. Alanazi’s study also drew the same conclusion 14.…”
Section: Discussionmentioning
confidence: 90%
“…In our multivariate analysis, the factors including age, hypertension, hyperlipemia, radiotherapy, and adenocarcinoma were independent risk factors for DVT in patients with gynecological malignant tumor. In a review of 9146 patients undergoing anterior cruciate ligament reconstruction, Bokshan suggested that increasing age over 30 years and hypertension were associated with an increased risk of DVT 13. Alanazi’s study also drew the same conclusion 14.…”
Section: Discussionmentioning
confidence: 90%
“…For instance, the American College of Chest Physicians indicated that it is not recommended to use thrombosis prevention measures for patients unless risk factors are present [7]. Several studies suggested that gender, age, BMI and other factors may be the potential risk factors of DVT [8][9][10][11][12]. Based on evidence existed, our purpose is to study the incidence of DVT in the two groups of anticoagulation and non-anticoagulation patients, as well as the risk factors of DVT formation after knee arthroscopic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In the relevant literature, the reported incidence of VTEs after TKA and ACL reconstruction was 0.36-62.5% [2][3][4], and 0.5% [1,6], respectively. The risk factors associated with VTEs after TKA included advanced age (> 70 years), drain use, and delayed ambulation (≥ 72 h) after surgery [4].…”
Section: Introductionmentioning
confidence: 99%